THE RELATIONSHIP BETWEEN FAMILY SOCIAL SUPPORT AND COMPLIANCE OF CHRONIC RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS - Dewanto, Adhe; Indrawati, Lina; Nuryanti, Lisna (Universitas Airlangga, 2025)
Introduction: Chronic kidney disease is defined as kidney damage that lasts long (chronic) and is characterized by a decrease in the kidney's ability to filter blood (GFR). Patients who experience this disease need social support from their families and compliance in undergoing hemodialysis. Therefore, this study aims to determine the relationship between family social support and compliance of chronic kidney failure patients undergoing hemodialysis at Cibitung Medika Hospital. Methods: The research method used in this study is descriptive correlation. The population in this study were all chronic renal failure patients with stable conditions who did outpatient hemodialysis at Cibitung Medical Hospital in the last 3 months, a total of 99 patients. Results: Based on statistical tests, a p-value of 0.000 with (p < 0.05) means Ha is accepted and Ho is rejected, meaning that there is a relationship between family support and the loyalty of chronic kidney failure patients undergoing hemodialysis at Cibitung Hospital in 2023. Conclusions: The conclusion in this study is that the majority of families being observed in this study provide full support to patients undergoing hemodialysis and most of chronic kidney failure patients comply with hemodialysis treatment at Cibitung Medika Hospital.